Technology Driven Consumer Protection for the Use of E-Commerce Platforms - Csorba, Luiela Magdalena; Vaduva, Florin; Dinu, Vasile; Dabija, Dan-Cristian (Transformations In Business & Economics, 2025)
In the context of the unprecedented development of online commerce, the need to implement consumer protection strategies while recognising and strengthening their rights is growing. This study aims to highlight the role of consumer protection in online purchasing transactions conducted on different e-commerce platforms using technology based on artificial intelligence (AI) systems and e-advertising. The authors’ approach is to use a conceptual model and argue its relationships. To conduct the research, the authors employed a survey technique involving an online questionnaire distributed to 354 consumers. The analysis of the relations between the constructs of the conceptual model is carried out using structural equations via the lavaan library, version 06-12 of the R software. The research results emphasise that both artificial intelligence-based systems and e-advertising are influenced by the way consumer protection is achieved, and, in turn, influence consumer perception and confidence in online platforms. The paper extends the research on the Technology Acceptance Model by firstly investigating the relationships between constructs such as the commitment of e-commerce platforms and unawareness of consumers’ rights when shopping online, and e-advertising; unawareness of consumers’ rights when shopping online and trust in the chatbots of e-commerce platforms; and the respect of consumers’ rights by e-commerce platforms and the increasing importance of e-advertising.